Genetic Susceptibility to Clozapine-Induced Agranulocytosis/Neutropenia Across Ethnicities: Results From a New Cohort of Turkish and Other Caucasian Participants, and Meta-Analysis. Issue 1 (6th June 2020) - Okhuijsen-Pfeifer, Cynthia; Ayhan, Yavuz; Lin, Bochao D; van Eijk, Kristel R; Bekema, Erwin; Kool, Lindy J G B; Bogers, Jan P A M; Muderrisoglu, Ahmet; Babaoglu, Melih O; Van Assche, Evelien; Medic, Jelena; Veerman, Selene; et al.
Abstract: Clozapine (CLZ) is considered the most effective antipsychotic, but its use is associated with neutropenia (CIN) and agranulocytosis (CIA). Although the exact etiology of these hazardous side effects is unknown, 4 genetic polymorphisms have been implicated by genome-wide association studies (GWAS), mostly performed in North-Western Europeans. These polymorphisms are rs113332494 ( HLA-DQB1 ), rs41549217 ( HLA-B ), and rs1546308/rs149104283 ( SLCO1B3/7 ), several of which were not directly genotyped but imputed. To test whether these 4 single-nucleotide polymorphisms (SNPs) are associated with CIN/CIA in a Turkish population and in a more extensive group of Caucasians, we directly genotyped these polymorphisms using Taqman and Sanger sequencing and performed logistic regression. We divided our participants (234 CLZ-using participants of whom 31 CIN/CIA cases) into (1) North-Western European, (2) Turkish, (3) Caucasian (=1 + 2); and (4) a total group (Caucasian + other ethnicities). Rs113332494 ( HLA-DQB1 ) was significantly associated with CIN/CIA in the total group ( P = 3.5 × 10 −8 ), in the Caucasian group ( P = 9.3 × 10 −6 ) and in the Turkish group ( P = 2.8 × 10 −5 ). Rs41549217 ( HLA-B ) was nominally significant in the Caucasian group ( P = .018). In meta-analysis of our results and the previously reported genome-wide results, 3 SNPs were significantly associated with CIN/CIA in participants with Caucasian ancestry: rs113332494 ( P = 2.05 × 10 −8 ), rs41549217 ( P = 7.19 × 10 −9 ), and rs149104283 ( P = 5.54 × 10 −9 ), with the result for rs1546308 ( SCLO1B3/SCLO1B7 ) being significantly heterogeneous across studies. Our results hint at ethnicity-dependent and clinically relevant effects of genetic polymorphisms on the risk to develop CIN/CIA. Pharmacogenetic testing can complement clinical decision making and thus empower appropriate CLZ prescribing, but ancestry should be taken into account when performing such testing for CLZ.